Educate, Re-educate, Then Re-educate: Organ Donation-centered Attitudes Should Be Established in Society - Tontus, H Omer (Elsevier BV, 2020)
The objectives of the study are to evaluate knowledge and attitudes toward organ and tissue donation, to pursue a deeper understanding of attitudes toward organ donation, and to gain an understanding of the underlying, personal reasoning for the desired action in organ donation among the adult population.Four thousand people were interviewed who were selected by the simple random sample type. A survey was conducted by voluntary, face-to-face interviews using a printed 25-item questionnaire form presented to street-recruited individuals over 18 years of age.In the study, where male/female distribution was represented equally, the majority of participants consisted of young and middle-aged, primary school graduates between the ages of 25 to 44 years. Although 91.1% of the respondents stated that they support organ donation, only 75.3% stated they wanted to donate organs. Organ donation-centeredness rates were low in those who did not finish a primary school education, people with a low household income, and those ≥65 years age group. A majority of the respondents (91.2%) were found to be against financial incentives for organ donation. Although 91.4% of the participants stated that organ donation is important if the recipient is a relative, this ratio decreased to 86.7% for a nonrelative. In our study, the level of accepting an organ as a recipient from an unknown person was 9.1% higher than the rate of willingness to donate to an unknown person. Surprisingly, despite 84% saying their religion is not against organ donation, 38.4% of the respondents cited religious concerns as the main reason for unwillingness and 58% of them indicated that they were reluctant to donate organs due to religious beliefs.It is important to know that it is not certain that anyone who is hypothetically in favor of organ donation will donate when faced with a real choice. Increasing the number of donors is the most important issue in order to benefit more patients in transplantation, which has achieved a very important success level through serious efforts. The majority of Turkey's population know about organ donation, support transplantation, and would be willing to donate their organs. Most of the respondents find it religiously correct and believe that it is an acceptable lifesaving procedure. However, a high percentage did not know how to donate, and they indicated that the information available on the subject is insufficient. Mass media campaigns and educational activities could resolve this matter and increase organ donation. According to the results of our study, when considering the number of patients who died while waiting for transplantation, organ donation awareness projects that are focused on converting knowledge to behavior are believed to be very critical. It is important to provide organ donation-oriented training at every educational level.
Keywords: Adult; Male; Health Knowledge, Attitudes, Practice; Tissue and Organ Procurement; Turkey; Middle Aged; Tissue Donors; Surveys and Questionnaires; Humans; Female